Dielectric and non-ohmic properties of Ca2Cu2Ti4-xSnxO12 (0.0 ≤ x ≤4.0) multiphasic ceramic composites - Cortés, J. A. [UNESP]; Cotrim, G. [UNESP]; Orrego, S. [UNESP]; Simões, A. Z. [UNESP]; Ramírez, M. A. [UNESP] (Elsevier, 2018)
Multiphasic Sn4+ substituted Ca2Cu2Ti4-xSnxO12 (0.0 ≤ x ≤ 4.0) ceramic composites were prepared by solid-state reaction. Their crystalline structure, microstructure, dielectric and non-ohmic properties were investigated. The electric properties and the densification and grain growth mechanisms were strongly influenced by a mixture of multiple phases, as evidenced by X-ray diffraction (XRD). The materials with low Sn4+ contents (x = 0.1 and 0.2) presented giant dielectric permittivity values, 166381 and 140845 respectively. This should be associated to insulating grain boundaries with activation energies of 0.58 eV and 0.30 eV respectively, as well as conductive grains with activation energies of 0.04 eV and 0.08 eV. On the other hand, samples with higher ionic substitution (x = 3.8, 3.9 and 4.0) revealed a new type of tin-based ceramic composites, which exhibit non-linear coefficients (α) of 3.0, 4.0 and 4.0, respectively. A new multiphase ceramic composites with high dielectric performance and non-ohmic properties are summarized.
Keywords: (micro)structural characterization; CCTO/CTO; Dielectric and non-linear behavior